1995
DOI: 10.1523/jneurosci.15-08-05612.1995
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides phase shift the mammalian circadian pacemaker

Abstract: We studied the influence on circadian rhythms of peptides that have been reported to be colocalized in suprachiasmatic nucleus (SCN) neurons. Gastrin-releasing peptide (GRP1–27), peptide histidine isoleucine (PHI), and vasoactive intestinal polypeptide (VIP) were microinjected into the suprachiasmatic nucleus (SCN) region of Syrian hamsters free running under three different constant lighting conditions. All peptide injections caused phase-dependent phase shifts of hamster locomotor activity rhythms which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(191 citation statements)
references
References 55 publications
12
177
1
1
Order By: Relevance
“…night (Piggins and Rusak, 1993;Piggins et al, 1994Piggins et al, , 1995Albers et al, 1995;McArthur et al, 2000). It has also been shown that the phase-shifting effects of a gastrin-releasing peptide injection can be blocked by the application of the gastrin-releasing peptide antagonist [D-F5Phe6,D-Ala11]BN(6 -13)OMe (Piggins et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…night (Piggins and Rusak, 1993;Piggins et al, 1994Piggins et al, , 1995Albers et al, 1995;McArthur et al, 2000). It has also been shown that the phase-shifting effects of a gastrin-releasing peptide injection can be blocked by the application of the gastrin-releasing peptide antagonist [D-F5Phe6,D-Ala11]BN(6 -13)OMe (Piggins et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the phase-shifting effects of a gastrin-releasing peptide injection can be blocked by the application of the gastrin-releasing peptide antagonist [D-F5Phe6,D-Ala11]BN(6 -13)OMe (Piggins et al, 1995). In mice, gastrin-releasing peptide injections induce mPer1 gene expression in dorsal SCN neurons, and gastrin-releasing peptide receptor-deficient mice show both blunted mPer1 and behavioral phase-shifting responses (Aida et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results demonstrate that controlled VIP pulses cause phase shifts similar to those resulting from light pulses, suggesting that the VIP signal and target are similar to those of light and may be modelled correspondingly. The target of VIP signalling is therefore assumed to be per transcription (Piggins et al 1995). Experimental data demonstrate that isolated (uncoupled) neurons exhibit both a broad distribution of periods and temporal (cycle-to-cycle) variability (Herzog et al 2004).…”
Section: Modelling Coupled Stochastic Mammalian Neuronsmentioning
confidence: 99%
“…The peptide and activation of the associated receptor also resets the circadian clock in vitro and in vivo in a pattern resembling that of photic stimulation (McArthur et al 2000;Piggins et al 1995). In hamsters this mechanism involves the NMDA receptor (Kallingal and Mintz 2006).…”
mentioning
confidence: 92%